Diagnosis and Surgical Management of a Retroperitoneal Lipoma in Pregnancy - Katharina Mitchell; Kylie Fuller; Alan Thomay; Robert Shapiro (Case Reports in Obstetrics and Gynecology)
Retroperitoneal lipomas during pregnancy are very rare. We report a case of a 29-year-old pregnant female who presented with a retroperitoneal lipoma. Our patient presented at 15-week gestation with abdominal pain, distention, and orthopnea. Due to vague symptoms and nonspecific imaging capabilities, retroperitoneal tumors in pregnancy are uniquely challenging with regard to diagnosis and treatment. We describe the unique work up of a retroperitoneal lipoma in pregnancy and the risks and benefits which were considered when optimizing care to the patient. Percutaneous core needle biopsy has accuracy rates for pathologic diagnosis of up to 98% and is largely safe to perform during pregnancy. Surgical resection of this type of tumor does not mandate cesarean delivery in subsequent pregnancies.